How Much Should We Teach the Enigma Machine? - Jeffrey A. Livermore (Journal of Cybersecurity Education, Research & Practice, 2017)
Developing courses and programs in Information Assurance can feel like trying to force ten pounds of flour into a five pound sack. We want to pack more into our courses than we have time to teach. As new technologies develop, we often find it necessary to drop old technologies out of the curriculum and our students miss out on the historical impacts the old technologies had. The discipline is so broad and deep that we have to carefully choose what concepts and technologies we study in depth, what we mention in passing, and what we leave out. Leaving out important historical developments deprives our students of historical context and the evolution of technology into the profession. This paper presents an argument for including the Enigma Machine in our curriculum.